Adiabatic Gasification and Pyrolysis of Coffee Husk Using Air-Steam for Partial Oxidation - Catalina Rodriguez; Gerardo Gordillo (Journal of Combustion)
Colombian coffee industry produces about 0.6 million tons of husk (CH) per year which could serve as feedstock for thermal gasification to produce gaseous and liquid fuels. The current paper deals with: (i) CH adiabatic gasification modeling using air-steam blends for partial oxidation and (ii) experimental thermogravimetric analysis to determine the CH activation energy (E). The Chemical Equilibrium with Applications Program (CEA), developed by NASA, was used to estimate the effect of equivalence ratio (ER) and steam to fuel ratio (S : F) on equilibrium temperature and gas composition of ~150 species. Also, an atom balance model was developed for comparison purposes. The results showed that increased ER and (S : F) ratios produce mixtures that are rich in H2 and CO2 but poor in CO. The value for the activation energy was estimated to be 221 kJ/kmol.